Gambaran Tingkat Pengetahuan Keselamatan dan Kesehatan Kerja Pada Petugas Pengambil Sampah Kota Samarinda: Overview of the Level of Occupational Safety and Health Knowledge of Waste Collectors in Samarinda City - Bramiasto, Muhammad Raka; Duma, Krispinus; Danial (ITKES Wiyata Husada Samarinda, 2024)
Occupational Safety and Health (OSHE) is a form of improving and maintaining the rights of all workers physically, mentally and socially, supervising people, work tools, materials and the work environment so that every worker is free from physical, mental, emotional or painful disturbances in conditions physiological and psychological workers, in order to prevent work-related accidents. Garbage collector are vulnerable jobs with various risks of work accidents, because they are directly exposed to community waste disposal. The purpose of this study was to describe the level of OSHE knowledge of garbage collectors in Samarinda City. The research design is descriptive observational with 80 research respondents. Using a simple random sampling technique using a questionnaire. This is a one-variable descriptive observational study. The results of this study show that the OSHE knowledge level of Garbage Collectors is (94%) in the